TikTok as an Islamic Da’wah Media in Shaping Religious Imitation, Sympathy, and Empathy Among Generation Z - Masrufah, Masrufah; Syarif , Zainuddin; Hasan, Nor (Fakultas Dakwah Institut Agama Islam Sunan Giri Ponorogo, 2024)
The development of digital media has transformed Islamic preaching from conventional methods into interactive and participatory communication spaces. Among these platforms, TikTok has become one of the most influential media for da’wah, especially among Generation Z. This study aims to analyze the role of TikTok as an Islamic da’wah medium in fostering religious imitation, sympathy, and empathy among young Muslims. This study examines TikTok’s role as an Islamic da’wah medium in shaping religious imitation, sympathy, and empathy among Generation Z audiences. Employing a qualitative content analysis of selected Islamic da’wah accounts alongside in-depth interviews with Generation Z users, this research explores how religious messages are presented, internalised, and emotionally responded to on the platform. The findings indicate that TikTok facilitates religious imitation through repetitive exposure to visible religious practices, encourages sympathy by presenting relatable moral narratives, and fosters empathy through emotionally resonant storytelling and interactive features such as comments and duets. Using a qualitative approach with a field research design, data were collected through in-depth interviews with followers of TikTok da’wah creators and observations of their content and user interactions. The findings show that TikTok-based digital da’wah plays a significant role in shaping Generation Z’s religious awareness through positive forms of social imitation. Qur’anic values such as hikmah (wisdom) and maw‘izhah hasanah (good counsel) are contextually represented, making da’wah more engaging, educational, and capable of fostering religious reflection among young social media users. Therefore, TikTok as a medium of Islamic da’wah plays an essential role in nurturing a reflective, empathetic, and contextually relevant form of religiosity within the dynamics of digital culture.